SUBLIME AND GROTESQUE: THE AESTHETIC DEVELOPMENT OF WEIRD FICTION IN THE WORK OF H.P. LOVECRAFT AND CHINA MIÉVILLE // SUBLIME E GROTESCO: O DESENVOLVIMENTO ESTÉTICO DA "WEIRD FICTION" NAS OBRAS DE H. P. LOVECRAFT E CHINA MIÉVILLE - Wight, Linda; Gadd, Nicole (Abusões, 2017)
RECEBIDO EM 17 FEV 2017 APROVADO EM 30 MAR 2017 Weird Fiction is identifiable by its atomosphere of cosmic fear and unease which is produced through the sublime and grotesque. H.P. Lovecraft's Weird Fiction invokes the sublime through other-worldly creatures that inspire awe and terror; beyond the grasp of limited human consciousness, they are both unfathomable and unspeakable. Cosmic fear is further heightened in Lovecraft's fiction through transgressive meldings of human and animal bodies into grotesque creatures which refute the laws of nature and systems of classification by which humans understand their world. While the sublime and grotesque remain crucial elements of recent Weird Fiction, China Mieville responds to Lovecraft's oeuvre by exploring the loss of the sublime in the postmodern era and positioning the grotesque as, not only a cause for horror, but also a source of creative potential and rebellion. This essay compares Kraken (2010), in which Mieville playfully engages with the Cthulhu mythos, with four of Lovecraft's most celebrated Weird stories, "Pickman's Model" (1927), "The Call of Cthulhu" (1928), "The Dunwich Horror" (1929) and "The Shadow Over Innsmouth" (1936). In both Lovecraft's early and Mieville's more recent Weird Fiction, the sublime and the grotesque play a significant role in creating the Weird aesthetic. However Mieville's interrogation of the sublime as it appears in Lovecraft's work, as well as his exploration of the technological grotesque and framing of the grotesque as an opportunity for self-empowerment and emancipation, marks his Weird Fiction as distinctly of its own time. // “Weird Fiction” é identificável pela sua atmosfera de medo cósmico e inquietação que são produzidas pelo sublime e grotesco. “Weird Fiction” de H. P. Lovecraft invoca o sublime através de criaturas de outro mundo que inspiram admiração e medo; além da compreensão limitada da consciência humana, eles são incomensuráveis e indescritíveis. O medo cósmico é aumentado na ficção de Lovecraft através das fusões transgressivas dos corpos humanos e animais em criaturas grotescas que refutam as leis da natureza e sistemas de classificação pelos quais os humanos entendem seu mundo. Enquanto o sublime e o grotesco permanecem, elementos cruciais da recente “Weird Fiction”, China Miéville responde a obra de Lovecraft explorando a perda do sublime na era pós-moderna e posicionando o grotesco, como não somente causa de horror, mas também como fonte de potencial criativo e rebelião. Este artigo compara Kraken (2010), no qual Miéville brinca com o mito de Cthulhu, com quatro das histórias “Weird” mais famosas de Lovecraft, “O Modelo de Pickman” (1927), “O Chamado de Cthulhu” (1928), “O Horror de Dunwich” (1929) e “A sombra de Innsmouth” (1936). Tanto na “Weird Fiction” inicial de Lovecraft quanto a mais recente de Miéville, o sublime e grotesco tem um papel significante na criação estética de “Weird”. Entretanto, o interrogatório do sublime de Miéville como aparece nas obras de Lovecraft, assim como a sua exploração do grotesco tecnológico e a concepção do grotesco como uma oportunidade para auto fortalecimento e emancipação, marca sua “Weird Fiction” distintamente de sua própria época. DOI: 10.12957/abusoes.2017.27428